Novel insights into histone lysine methyltransferases in cancer therapy: From epigenetic regulation to selective drugs - Qili Liao; Jie Yang; Shengfang Ge; Peiwei Chai; Jiayan Fan; Renbing Jia (Elsevier, 2023)
The reversible and precise temporal and spatial regulation of histone lysine methyltransferases (KMTs) is essential for epigenome homeostasis. The dysregulation of KMTs is associated with tumor initiation, metastasis, chemoresistance, invasiveness, and the immune microenvironment. Therapeutically, their promising effects are being evaluated in diversified preclinical and clinical trials, demonstrating encouraging outcomes in multiple malignancies. In this review, we have updated recent understandings of KMTs' functions and the development of their targeted inhibitors. First, we provide an updated overview of the regulatory roles of several KMT activities in oncogenesis, tumor suppression, and immune regulation. In addition, we summarize the current targeting strategies in different cancer types and multiple ongoing clinical trials of combination therapies with KMT inhibitors. In summary, we endeavor to depict the regulation of KMT-mediated epigenetic landscape and provide potential epigenetic targets in the treatment of cancers.